DISKURSUS FEMINISME PEREMPUAN PADA ABAD 19 DALAM FILM “LITTLE WOMEN” - Dwi Pela Agustina; Stara Asrita (Metacommunication: Journal of Communication Studies, 2023)
This study aims to find out how the discourse of 19th century women in Little Women movie. The analytical method is using critical discourse analysis method of Norman Fairclough's model with three dimensional models, dimensions of text, discourse practice and socio-cultural practice.  The results show that the emerging feminist discourse is liberal feminism.  The text dimension shows that Jo March not wanting to get married, struggling alone, being able to be empowered with his own abilities.  The dimension of discourse practice was not yet able to accept women to appear in public spaces, receive inadequate education and limited employment opportunities.  The socio-cultural practice, the people is still in the patriarchal ideology that dominates every level.